2021
DOI: 10.18332/popmed/134990
|View full text |Cite
|
Sign up to set email alerts
|

LifeFirst: Impact of a school-based tobacco and supari cessation intervention among adolescent students in Mumbai, India

Abstract: INTRODUCTIONThe youth are a vulnerable populationgroup for tobacco-related harms. Schools are an excellent setting for health promotion; yet there is a dearth of schoolbased cessation interventions, rarely evaluated for their impact. Here, we assess the impact of the LifeFirst program: an ongoing tobacco and supari (areca nut) cessation intervention delivered to students from corporation schools in Mumbai city. METHODS We used a prospective quasi-experimental design with an intervention and a control arm embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…One study also evaluated the feasibility of providing psychological intervention. 26 Two Indian studies 31,32 developed a school-based psychosocial cessation intervention plan to reduce AN intake among school children. Most studies demonstrated an increase in awareness related to the harms of AN, motivation to quit, and a reduction in AN use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study also evaluated the feasibility of providing psychological intervention. 26 Two Indian studies 31,32 developed a school-based psychosocial cessation intervention plan to reduce AN intake among school children. Most studies demonstrated an increase in awareness related to the harms of AN, motivation to quit, and a reduction in AN use.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective quasi-experimental study on 827 students in Mumbai, India, aimed to understand the impact of a school-based tobacco and AN (supari) cessation intervention among adolescent students. 31 The intervention was conducted for 7th, 8th, and 9th grade students using LifeFirst, a standardized tobacco and supari cessation program conceived and implemented by the Narotam Sekhsaria Foundation, India, since 2012, which includes the delivery of six group-based education and counseling sessions by trained counselors. The program aimed at providing educational intervention to corporation-funded/managed (local government) schools in Mumbai.…”
Section: Much Of the Research On Psychological Interventions For An C...mentioning
confidence: 99%
“…LifeFirst, a school-based tobacco-cessation program, initiated by Narotam Sekhsaria Foundation in coordination with Salaam Bombay Foundation helps adolescent tobacco-users to quit the habit through evidence-based counselling (Bhojani et al, 2021). During the course of implementing this cessation program, e-cigarette availability and use was reported by students.…”
Section: Introductionmentioning
confidence: 99%